Scent releasing silicone septa: A versatile method for bioassays with volatiles - Huber, Franz K.; Schiestl, Florian P. (Frontiers in Ecology and Evolution, 2022)
Volatile organic compounds are of great importance for communication within biological systems. For the experimental investigation of the functions of volatiles, methods for experimental manipulation are needed. Based on scent-release methods from pheromone research, Wwe describe here introduce a simple and cheap method for scent manipulation using that uses a small piece of silicone rubber (i.e. a silicone septum). Volatile compounds are applied on the septum by soaking the septa for one hour in a solvent/volatile solution. After removal of the septum from the solution and a drying period of one hour to allow for evaporation of the solvent, the silicone emits the volatiles at a continuously decreasing rate for a minimum of 24hrs. In this study we measure the variability of the emission and quantify the emission of 22 common floral scent compounds at four different time points and in four different soaking concentrations. Our results show that for the same compound and soaking concentration, variability of volatile emission was low, showing the method leads to repeatable emission rates and can be fine-tuned to a desired emission rate. We provide a calculation tool based on linear regression to allow an experimenter to calculate soaking concentration for each of the 22 compounds to achieve a desirable emission from the septa, as well as to estimate the emission rate of a volatile from the septa after a given time.